ANALISIS FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN BANK BENGKULU - Utami, Dearsa Putri; Fachruzzaman, Fachruzzaman; Puspita, Lisa Martiah Nila (JURNAL FAIRNESS, 2018)
This study aims to evaluate operating profit achievement and analyze financial performance factors of Main Branch of Bank Bengkulu. This type of research uses descriptive qualitative with an association approach. The result shows that the achievement of Main Branch of Bank Bengkulu isn’t achieved due to various factors. The results of the interview concluded the factors that led to the non-achievement of profit is factor of macroeconomic conditions, monetary policy, fiscal policies, competitors, human resources and strategies. The results of the association approach prove that there is a relationship between the profit achievement and employee performance.